1998
DOI: 10.1523/jneurosci.18-12-04767.1998
|View full text |Cite
|
Sign up to set email alerts
|

Aging Alters the Rhythmic Expression of Vasoactive Intestinal Polypeptide mRNA But Not Arginine Vasopressin mRNA in the Suprachiasmatic Nuclei of Female Rats

Abstract: Our laboratory has shown that the ability of the suprachiasmatic nuclei (SCN) to regulate a number of rhythmic processes may be compromised by the time females reach middle age. Therefore, we examined the effects of aging on the rhythmic expression of two neuropeptides synthesized in the SCN, vasoactive intestinal polypeptide (VIP) and arginine vasopressin (AVP), using in situ hybridization. Because both VIP and AVP are outputs of the SCN, we hypothesized that age-related changes in rhythmicity are associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
92
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 74 publications
11
92
5
Order By: Relevance
“…Symbols indicate levels of significance between time points (*p Ͻ 0.05; **p Ͻ 0.01; ***p Ͻ 0.001) and between treatments ( ## p Ͻ 0.01; ### p Ͻ 0.001). ( Krajnak et al, 1998a), at the same age we observed the disappearance in cAMP rhythms in the current study. VIP dynamics are sexually dimorphic and play essential roles in cyclic reproductive function in females.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Symbols indicate levels of significance between time points (*p Ͻ 0.05; **p Ͻ 0.01; ***p Ͻ 0.001) and between treatments ( ## p Ͻ 0.01; ### p Ͻ 0.001). ( Krajnak et al, 1998a), at the same age we observed the disappearance in cAMP rhythms in the current study. VIP dynamics are sexually dimorphic and play essential roles in cyclic reproductive function in females.…”
Section: Discussionsupporting
confidence: 84%
“…Our findings confirm and extend the previous study by Chappell et al (2000) who showed that cAMP levels display a diurnal rhythm in the AVPV. It is particularly intriguing that the disappearance of the cAMP rhythms occur at the same age as previously reported alterations in VIP rhythms in the SCN and in the activation of GnRH neurons, which is required for LH surges to occur (Lloyd et al, 1994;Krajnak et al, 1998aKrajnak et al, , 2001Le et al, 2001;Legan and Tsai, 2003). Therefore, we explored whether these three neurochemicals (VIP, cAMP, and GnRH) are functionally linked.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Two SCN peptides, VIP and AVP, have long been implicated in stimulation of the reproductive axis. VIP mRNA but not AVP mRNA becomes arrhythmic in the SCN of middle-aged female hamsters (Krajnak et al, 1998), and suppression of SCN VIP in young female hamsters results in accelerated deficits in GnRH activation and an LH surge that mimic that of an aged population (Gerhold et al, 2005;Harney et al, 1996). Together, these findings suggest that age-related deficits in the neuroendocrine mechanisms mediating ovulation may result from loss of function at the level of the SCN.…”
Section: The Circadian System and Reproductive Agingmentioning
confidence: 85%
“…Moreover, SCN have a reduced expression of two major neurochemical constituents, vasoactive intestinal polypeptide (Chee et al 1988;Krajnak et al 1998), and vasopressin (Roozendaal et al 1987;Cayetanot et al 2005), which accounts to a weakening of SCN interconnections, therefore affecting the circadian clock functionality (Engelberth et al 2013). Current data, however, are focused solely on the aging effects on SCN, which brings a limitation to understand the whole process of aging in CTS (Yamazaki et al 2002;Davidson et al 2008).…”
Section: Introductionmentioning
confidence: 99%